The evolution of sustainable awareness through key historical milestones - Silva, Cássia Mara Alexandrino; Ferreira, Allan Berthier Silva; Leão, Airton Pereira da Silva; Silva, Gustavo Perroni Gomes da; Estevam, Stênio Maia; Tourem, Rafael Viêro; Nascimento, Leonardo Dias; Eccard, Ana Flávia Costa; Durigon, Salesiano; Borges , Marllisson Eriques Araújo; Silva, Luciano Henrique Pereira da (Seven Editora, 2024)
The research aimed to analyze the trajectory of environmental movements throughout history, highlighting their impacts, public policies and awareness initiatives in the promotion of environmental conservation and sustainable practices. To this end, a bibliographic research was carried out through the survey of articles on the Scopus, SciELO and Google Scholar platforms. As a result, it has been found that, from the Industrial Revolution to recent events such as Rio+20 and the Paris Agreement, the historical context has shaped these movements and influenced global sustainability policies. The emergence of environmentalism as a political and social force was a response to the challenges of environmental degradation and the unbridled exploitation of natural resources. Events such as the Love Canal disaster and the Stockholm Conference boosted environmental activism, culminating in Rio-92, which laid solid foundations for international cooperation and important environmental agreements. The Kyoto Protocol was crucial in the fight against climate change, while the Johannesburg Earth Summit and Rio+20 reaffirmed the commitment to sustainable development and global cooperation. Despite advances, challenges such as climate change require collaborative approaches involving governments, the private sector, and civil society. Environmentalism and sustainability represent commitments to the future, requiring continuity in awareness, responsible public policies, and sustainable practices to achieve an equitable and environmentally sound future. DOI:https://doi.org/10.56238/sevened2023.001-020